Structural member and manufacturing method thereof
A structural member with a gradient thin film layer, formed by diffusing functional components into the base material using a pulsed laser, addresses peeling issues and enhances mechanical properties for improved cutting tool performance.
Patent Information
- Application Number
- JP2019092061
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-05-22
- Filing Date
- 2019-05-15
- Publication Date
- 2025-01-23
- Estimated Expiration
- 2039-05-15
AI Technical Summary
Conventional cutting tools with hard coatings often experience peeling during cutting operations.
A structural member with a thin film layer featuring a gradient structure, where the ratio of functional members with higher mechanical properties decreases from the surface to the interface, achieved by adsorbing functional components and irradiating with a pulsed laser to diffuse them into the base material.
The thin film layer effectively prevents peeling and enhances mechanical properties, improving wear resistance and extending the life of cutting tools.
Smart Images

Figure 0007620297000003 
Figure 0007620297000004 
Figure 0007620297000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a structural member having a thin film layer on the surface of an element made of a metal material or the like, and a method for manufacturing the same. [Background technology]
[0002] Conventionally, the surface of cemented carbide cutting tools has been coated with a hard material to improve cutting performance and extend the tool life.
[0003] Patent Document 1 describes a cemented carbide tool having a hard protective film made of metal nitride, metal carbide, or the like on the surface of a substrate.
[0004] Patent Document 2 describes a tool in which a tool substrate made of cemented carbide is subjected to a surface treatment by femtosecond laser peening and then coated with a hard coating. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2017-56499 A [Patent Document 2] JP 2013-107143 A Summary of the Invention [Problem to be solved by the invention]
[0006] Conventional hard coatings provided on the surfaces of cutting tools have been prone to peeling off when cutting is performed using the cutting tool. An object of the present invention is to solve the above problems and provide a structural member having a thin film layer that is not easily peeled off even when subjected to cutting processing. [Means for solving the problem]
[0007] The means for solving the problem are as follows. (1) A structural member having a thin film layer on the surface of a base member made of a metal material or a ceramic material, the thin film layer includes the elemental material and one or more functional members selected from the group consisting of atoms, molecules, and structures, the functional members having mechanical properties higher than those of the elemental material, A structural member, characterized in that the proportion of said functional material is high on the surface side of said thin film layer and low on the interface side with said base member, which is a gradient structure layer. (2) A structural member according to (1), characterized in that the base material is a cemented carbide.
[0008] (3) an adsorption step of adsorbing, on a surface of a base member made of a metal material or a ceramic material, one or more functional components selected from the group consisting of atoms, molecules, and structures, which have higher mechanical properties than the base member, in a solid, liquid, or gas phase state; a diffusion step of irradiating a surface onto which the functional component is adsorbed with a pulsed laser, or irradiating the surface with a pulsed laser while the functional component is being adsorbed, thereby causing the base material and the functional component to diffuse relative to each other, thereby forming a thin film layer in which the proportion of the functional component is high on the surface side and low on the interface side with the base material. (4) The method for manufacturing a structural member according to (3), characterized in that the pulse width of the pulse laser is from femtoseconds to nanoseconds and the wavelength is from 300 to 1200 nm. Effect of the Invention
[0009] According to the present invention, a structural member having a thin film layer that is not easily peeled off even when cutting is performed can be provided. Therefore, the structural member of the present invention is suitable as a material for cutting tools. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a conceptual diagram of a structural member according to a first embodiment of the present invention. [Diagram 2] 1 is a photograph showing an example of a manufacturing apparatus used for manufacturing a structural member of the present invention. [Diagram 3]1 is a photograph (magnification x50) of the surface of the thin film-layered carbide cutting tip (31) of Example 1. [Figure 4] FIG. 13 is a diagram showing the results of evaluation of the wear resistance of a thin film-layered carbide cutting tool tip. [Diagram 5] 1 is a photograph showing the evaluation results of polishing a carbide blade tip with a thin film layer using a CMP grinding wheel. [Figure 6] FIG. 1 is a diagram showing an evaluation method for turning using a carbide cutting tool tip with a thin film layer. [Figure 7] 1 is a graph showing the relationship between the cutting distance and the surface temperature of the workpiece of the tools of Example 3 and Comparative Examples 4 to 6. [Figure 8] 11 is a graph showing the results of analyzing the structural member of Example 4 using secondary ion mass spectrometry (SIMS). [Figure 9] 1 is a photomicrograph of a structural member of Example 5 observed with a stereo microscope. [Figure 10] 1 is a photomicrograph of the structural member of Example 5 observed with a differential interference microscope. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, the embodiments of the present invention will be described with reference to the drawings. The present invention is not limited to the following embodiments, and changes, modifications, and improvements can be made without departing from the scope of the invention.
[0012] (First embodiment) Fig. 1 shows a conceptual diagram of a structural member (1) according to a first embodiment of the present invention. Fig. 1(a) is a schematic cross-sectional view of the structural member (1) according to the first embodiment. Fig. 1(b) is a graph showing the relationship between the ratio of functional members in the structural member (1) and the thickness of the structural member (1). As shown in Fig. 1(a), the structural member (1) is composed of an elemental member (3) and a thin film layer (5) (corresponding to the "thin film layer" in the claims). The elemental member (3) is a metal material or a ceramic material. The thin film layer (5) is composed of the elemental member (3) and a functional member (10) whose mechanical properties are better (higher) than those of the elemental member (3).
[0013] In the thin film layer (5), the functional material (10) is diffused into the elemental material (3). As shown in FIG. 1(b), the diffusion state (ratio) of the functional material (10) in the structural member (1) is a gradient ratio, with the surface side of the thin film layer (5) being high and the interface side between the thin film layer (5) and the elemental material (3) being low. In other words, when the ratio of the functional material (10) in the surface area of the thin film layer (5) in the thickness direction of the thin film layer (5) (for example, the mass of the functional material per unit area) is 100%, the ratio of the functional material (10) is a gradient ratio that decreases toward the interface with the inner elemental material (3). In FIG. 1(b), as an example of the structural member (1), a case in which the ratio of the functional material (10) in the thin film layer (5) is proportional to the thickness of the thin film layer (5) is shown as an example, but the ratio of the functional material (10) in the thin film layer (5) does not have to be proportional to the thickness of the thin film layer (5).
[0014] The reason why the ratio of the functional material (10) in the thin film layer (5) has a graded structure depends on the manufacturing method of the structural member (1). That is, the functional material (10) is adsorbed on the surface of the elemental material (3), and the elemental material (3) and the functional material (10) are mutually diffused by irradiating them with a pulsed laser (23). When the functional material (10) and the elemental material (3) are irradiated with the pulsed laser (23), the electrons of the functional material (10) and the elemental material (3) are vibrated, and the electrons are excited to a higher density, which widens the atomic distance. Therefore, the elemental material (3) and the functional material (10) are mutually diffused at the atomic level, and the ratio of the functional material (10) in the thin film layer (5) has a graded structure as described above. Hereinafter, this is called doping.
[0015] The thin film layer (5) formed by doping integrally bonds the base member (3) and the functional member (10) therein. The interface between the thin film layer (5) and the base member (3) is also integrally bonded. Therefore, the functional member (10) will not fall off from the structural member (1), and the thin film layer (5) will not peel off from the structural member (1).
[0016] The base member (3) is made of a metal material or a ceramic material. Examples of metal materials include cemented carbide, stainless steel, and high speed steel (HSS). Cemented carbide is a sintered mixture that mainly contains tungsten carbide (WC) and cobalt (Co) as a binder. Ceramic materials are appropriately selected from inorganic compounds such as metal or nonmetal oxides, carbides, nitrides, and borides. Oxide-based materials include alumina, zirconia, and barium titanate, carbide-based materials include silicon carbide, and nitride-based materials include silicon nitride. A typical example is cermet (oxide ceramics).
[0017] The functional component (10) used for doping is one or more types of functional component (10) selected from the group consisting of atoms (11), molecules (13), and structures (15), and is a material having higher mechanical properties than the elemental component (3) in order to improve the mechanical properties of the elemental component (3). Mechanical properties include hardness, toughness, wear resistance, corrosion resistance, etc. Examples of the functional component (10) include boron (B), boron nitride (BN), nitrogen (N), carbon (C), oxygen (O), and silicon (Si).
[0018] Second embodiment The second embodiment specifies the type of the functional component (10) and the state of the functional component (10) when the functional component (10) is adsorbed onto the surface of the base material (3).
[0019] The type of functional component (10) is preferably an atom (11), a molecule (13), or a structure (15) from the viewpoint of penetrating into the bond structure of the constituent atoms of the elemental component (3) (hereinafter, sometimes referred to as "atom (11) or the like"). Examples of the atom (11) include boron (B) and nitrogen (N), examples of the molecule (13) include boron nitride (BN), boron silicide (SiB), and silicide carbon (SiC), and examples of the structure (15) include silicon nitride (Si3N4).
[0020] The atmosphere around the functional component (10) when the functional component (10) is adsorbed onto the surface of the base material (3) is preferably in a solid, liquid or gas phase. The term "solid phase atmosphere" refers to the use of atoms (11) etc. in a solid state, such as a powder, as the functional member (10). The term "liquid phase atmosphere" refers to the use of atoms (11) etc. in a suspended, dispersed or dissolved state in a solvent as the functional member (10). The term "gas phase atmosphere" refers to the use of atoms (11) etc. in a vaporized state in a gas, etc. as the functional member (10).
[0021] Third embodiment 2 is a photograph showing an example of a manufacturing apparatus (optical system) used when manufacturing the structural member (1) of the present invention. In the optical system used when manufacturing the structural member (1) of the present invention, it is important not to change the relative positions of the lens (21) and the pulse laser (23).
[0022] The pulse time of the pulsed laser (23) contributes to the high density excitation of electrons in the base material (3) and the functional material (10). A long pulse spreads heat, while a short pulse narrows the heat spread. Therefore, a long pulse has a large effect of thermal diffusion from the irradiation spot. Thermal expansion is when electrons are excited and the atomic spacing becomes wider.
[0023] Therefore, in order to dope the elemental material (3) and the functional material (10) in a high-density excited state, the pulse width of the pulse laser (23) is preferably from femtoseconds to nanoseconds. This is because the periodic time of lattice vibration, which depends on the excitation of electrons, is approximately several hundred femtoseconds to several picoseconds, and a pulse width on the order of nanoseconds is sufficient. In addition, the wavelength of the pulse laser (23) is preferably from 300 to 1200 nm. When the wavelength is from 300 nm to 1200 nm, the penetration depth of light into tungsten is from 10 nm to 15 nm. EXAMPLES
[0024] Example 1 Example 1 shows a method for manufacturing a structural member (1) having a thin film layer (5) using the manufacturing apparatus shown in Fig. 2. A metal material, a carbide blade tip (30) (Comparative Example 1 (DNGA150404HiT10: product name, manufactured by Mitsubishi Materials Corporation)) was used as the base member (3), and boron nitride (BN: molecules), which has higher mechanical properties (hardness and wear resistance) than the carbide blade tip (30), was adsorbed in a solid state onto the surface of the base member (3) as the functional member (10) (adsorption process). Next, the surface with the boron nitride adsorbed thereon was irradiated with a pulsed laser (23) (pulse width: 500 picoseconds, wavelength: 0.532 μm), causing the metal material forming the carbide blade tip (30) and the boron nitride to diffuse into each other, generating a thin film layer (5). That is, a carbide blade tip (31) with a thin film layer (5) (Example 1) was produced as a structural member (1) with a thin film layer (5). The carbide blade tip (30) was made of tungsten carbide (WC) and cobalt (Co).
[0025] Specifically, boron nitride (average particle size 10 μm) dispersed in a solvent made of ethanol was applied to the cemented carbide blade tip (30) using a spin coater and allowed to adsorb. The application of the boron nitride dispersed in the solvent was performed with a boron nitride concentration of 2 g / L in the solvent, a spin coater rotation speed of 200 rpm, and an application time of 20 seconds so that overlapping of boron nitride particles on the surface of the cemented carbide blade tip (30) was not observed under a stereomicroscope. A pulsed laser (23) with a pulse width of 500 picoseconds and a wavelength of 0.532 μm was irradiated from above the applied and adsorbed boron nitride for about 1 minute to produce a cemented carbide blade tip (31) with a thin film layer (5).
[0026] Fig. 3 is a photograph of the surface of the carbide blade tip (31) with a thin film layer of Example 1 observed at a magnification of 50 times. As shown in Fig. 3, many scratches were engraved on the surface of the carbide blade tip (31) with the thin film layer (5) of Example 1 when the carbide blade tip (30) (Comparative Example 1) before the formation of the thin film layer (5) was molded with a diamond grindstone. When the surface of the carbide blade tip (31) with the thin film layer of Example 1 (surface of the thin film layer (5)) was observed, the scratches exhibited a blue interference color (for example, the portion indicated by reference symbol 32 in Fig. 3). This is due to doping with boron nitride.
[0027] (Evaluation of wear resistance) The wear resistance was evaluated for the carbide cutting tip (31) with the thin film layer of Example 1. Specifically, chemical mechanical polishing (sometimes referred to as "CMP") was performed using fixed silica as a CMP grindstone for two types of carbide cutting tip (31) with the thin film layer (5) of Example 1 and the carbide cutting tip (30) without the thin film layer (5) of Comparative Example 1, and the wear state was evaluated.
[0028] FIG. 4(a) shows the results of evaluation of the wear resistance of the carbide blade tip (31) with the thin film layer (5) of Example 1. The left side of FIG. 4(a) shows the state before chemical mechanical polishing, and the right side of FIG. 4(a) shows the state after 30 minutes of chemical mechanical polishing. As shown in FIG. 4(a), the shape of the scratches formed by the diamond grindstone was almost unchanged before and after chemical mechanical polishing. Therefore, it was determined that the carbide blade tip (31) with the thin film layer (5) of Example 1 is resistant to wear.
[0029] FIG. 4(b) shows the results of evaluation of the wear resistance of the carbide blade tip (30) without the thin film layer (5) of Comparative Example 1. The left side of FIG. 4(b) shows the state before chemical mechanical polishing, and the right side of FIG. 4(b) shows the state after 30 minutes of chemical mechanical polishing. As shown in FIG. 4(b), after chemical mechanical polishing, the scratch shape formed by the diamond grindstone had disappeared. Therefore, the carbide blade tip (30) without the thin film layer (5) of Comparative Example 1 had worn down. Also in comparison between the right side of FIG. 4(a) (Example 1) and the right side of FIG. 4(b) (Comparative Example 1), it was determined that the carbide cutting tip (31) with the thin film layer (5) of Example 1 was less susceptible to wear than the carbide cutting tip (30) without the thin film layer (5) of Comparative Example 1.
[0030] (CMP effect) We optimized the shape of the grinding wheel used in chemical mechanical polishing (hereinafter sometimes referred to as "CMP grinding wheel") and quantified the processing conditions. To examine the sharpening of the tool cutting edge (the effect of CMP), the same commercially available carbide tip as in Comparative Example 1 was finished using a carbide cutting tool tip (30) as a CMP grindstone and observed under a microscope. Fig. 5(a) is a photograph of the rake face of the same commercially available carbide tip as in Comparative Example 1 when sharpened using the carbide blade tip (30) of Comparative Example 1 as a CMP grindstone. Fig. 5(c) is a photograph of the flank face of the same commercially available carbide tip as in Comparative Example 1 when sharpened using the carbide blade tip (30) of Comparative Example 1 as a CMP grindstone. In Figs. 5(a) and 5(c), the observations were made with a stereo microscope at a magnification of 20x.
[0031] In addition, the same commercially available carbide tip as in Comparative Example 1, which was finished using the carbide blade tip (31) of Example 1 as a CMP grindstone, was observed under a microscope. FIG. 5(b) is a photograph of the rake face of the same commercially available carbide tip as in Comparative Example 1 when sharpened using the carbide blade tip (31) of Example 1 as a CMP grindstone. FIG. 5(d) is a photograph of the flank face of the same commercially available carbide tip as in Comparative Example 1 when sharpened using the carbide blade tip (31) of Example 1 as a CMP grindstone. In FIG. 5(b) and FIG. 5(d), the observation with a stereo microscope is at a magnification of 20 times. FIG. 5(e) is an enlarged photograph of the cutting edge formed by the rake face (FIG. 5(b)) and flank face (FIG. 5(d)) of the same commercially available carbide tip as in Comparative Example 1 when sharpened using the carbide blade tip (31) of Example 1 as a CMP grindstone. In FIG. 5(e), the observation was performed at a magnification of 1000 times using a scanning electron microscope (SEM).
[0032] The grinding conditions for the commercially available carbide tips in Figures 5(a) to (e) are shown in Table 1. From FIGS. 5(a) and (c), it can be seen that when the carbide blade tip (30) of Comparative Example 1 is used as the CMP grindstone, various grinding marks that were generated when the cutting edge was formed remain. 5(b), (d), and (e) show that the commercially available carbide tip using the carbide blade tip (31) of Example 1 as the CMP grindstone has no grinding roots and has a flat surface. Also, as shown in FIG. 5(b), (d), and (e), it can be seen that the cutting edge of the commercially available carbide tip is sharp without chipping. When the carbide blade tip (31) of Example 1 was used as the CMP grindstone, the curvature of the cutting edge (cutting edge roundness) was R50 nm or less. From these results, it was found that by using the carbide cutting tip (31) of Example 1 as a CMP grinding wheel, it was possible to successfully reduce the curvature of the rounded cutting edge of the commercially available carbide tip compared to the case where the carbide cutting tip (30) of Comparative Example 1 was used.
[0033] [Table 1]
[0034] (Example 2, Comparative Examples 2 and 3) (Pulse laser doping effect) A commercially available tool (DNGA150404HiT10: product name, manufactured by Mitsubishi Materials Corporation) (Comparative Example 2), a tool obtained by sharpening the commercially available tool by chemical mechanical polishing as shown in Fig. 5(b), (d), and (e) (Comparative Example 3), and a tool obtained by forming a thin film layer (5) on the surface of the sharpened commercially available tool by the method described below (Example 2) were evaluated for their cutting distances by the method described below.
[0035] (Method of forming thin film layer (5) in Example 2) Boron nitride (average particle size 0.1 μm) was dispersed in ethanol to a concentration of 2 g / L, and 1 ml of the solution was applied to the surface of the sharpened commercial tool using a spin coater and then dried, causing boron nitride in a solid phase to be adsorbed onto the surface of the commercial tool. Next, a pulsed laser (23) with a pulse width of 500 picoseconds and a wavelength of 0.53 μm was irradiated onto the surface of the commercially available tool onto which solid-phase boron nitride had been adsorbed for one minute to form a thin film layer (5).
[0036] Fig. 6(a) is a photograph of a test piece (workpiece) used to evaluate the cutting distance with the tools of Example 2 and Comparative Examples 2 and 3. Fig. 6(b) is a diagram for explaining the cutting conditions of the test piece shown in Fig. 6(a). Table 2 shows the cutting conditions of Example 2 and Comparative Examples 2 and 3. In Table 2, the sharpened blade of Comparative Example 3 is shown as Nano-Edge, and the blade of Example 2, which was doped with pulsed laser, is shown as Nano-Edge+LD. As shown in Figure 6 and Table 2, the Inconel 718 workpiece was rotated at a rotational speed of 400 rpm, the cutting edge of the tool was inserted 20 μm, and the tool was moved horizontally (in the length direction of the workpiece) at a moving speed of 0.1 mm per rotation, performing dry cutting without cutting oil. The cutting conditions (cutting speed) were equivalent to the cutting speeds generally used in aircraft, etc. The cutting distance shown in Table 2 was determined as the distance up to the point where the surface became rough when visually inspected during cutting.
[0037] From the results of Comparative Example 2 and Comparative Example 3, it was found that the blade life can be roughly doubled by sharpening the blade by chemical mechanical polishing. Also, from the results of Comparative Example 2 and Example 2, it was found that the blade life can be roughly 10 times longer by adsorbing boron nitride in a solid phase and then doping the surface with a pulsed laser in addition to chemical mechanical polishing.
[0038] [Table 2]
[0039] (Example 3, Comparative Examples 4 to 6) A commercially available tool (DNGA150404HiT10: product name, manufactured by Mitsubishi Materials Corporation) (Comparative Example 4), tools sharpened by secco etching this commercially available tool under the conditions shown below (Comparative Examples 5 and 6), and a tool (Example 3) in which a thin film layer (5) was formed on the commercially available tool sharpened by secco etching in the same manner as in Example 2 were evaluated for cutting distance in the same manner as in Example 2, and the surface temperature of the workpiece was measured using a radiation temperature system. The results are shown in FIG. 7.
[0040] (Seco Etching Methods of Comparative Examples 5 and 6, and Example 3) The commercially available tool was immersed in a 15% KOH aqueous solution for 1 minute to perform secco-etching, which dissolves and removes defects.
[0041] 7 is a graph showing the relationship between the cutting distance and the surface temperature of the workpiece of the tools of Example 3 and Comparative Examples 4 to 6. As shown in FIG. 7, the surface temperature of the workpiece of Example 3 was lower than that of Comparative Examples 4 to 6. Moreover, in Example 3, the cutting distance was about three times that of Comparative Example 4.
[0042] Example 4 By applying electrical current, -6 Ti was evaporated in a vacuum of less than Torr, and the Ti functional component was adsorbed in a gaseous state onto the surface of silicon carbide (SiC), a ceramic material. A pulsed laser with a pulse width of 10 nanoseconds and a wavelength of 0.3 μm was then irradiated onto the surface for one minute, yielding a structural component of Example 4.
[0043] The structural member of Example 4 was analyzed using secondary ion mass spectrometry (SIMS). The results are shown in Figure 8. Figure 8 is a graph showing the relationship between the depth from the surface of the structural member of Example 4 and the concentrations of C, Si, and Ti. In the graph shown in Figure 8, the vertical axis on the left side shows the Ti concentration (number of atoms) per unit volume. The vertical axis on the right side shows the SIMS Yield, which is the number of ions (concentration) per second that enter the detectors for Si and C in single crystal silicon carbide (SiC). 8, the concentrations of C and Si in the structural member of Example 4 were approximately constant regardless of the depth from the surface. On the other hand, the concentration of Ti was high on the surface side and low on the interface side with silicon carbide, forming a gradient structure layer.
[0044] Example 5 A commercially available tool (DNGA150404HiT10: product name, manufactured by Mitsubishi Materials Corporation) was placed in a methylene blue aqueous solution to adsorb nitrogen as a functional material on the surface in a liquid phase. Next, a pulsed laser with a pulse width of 500 picoseconds and a wavelength of 0.53 μm was irradiated on the surface of the commercially available tool with nitrogen adsorbed while still immersed in the methylene blue aqueous solution for 1 minute, and the tool was taken out of the methylene blue aqueous solution and dried to obtain a structural member of Example 5.
[0045] The surface of the structural member of Example 5 was observed using a stereo microscope and a differential interference contrast microscope (DIC), and the results are shown in Figs. Figures 9(a) and 9(b) are micrographs of the structural member of Example 5 observed with a stereo microscope. In Figure 9, the light gray parts indicated by the arrows are regions where nitrogen exists as a functional member. Figures 10(a) and 10(b) are micrographs of the structural member of Example 5 observed with a differential interference microscope. In Figure 10, the parts indicated by the arrows are regions where nitrogen exists as a functional member because they have a refractive index different from that of the base material. As shown in Figures 9 and 10, it was confirmed that a thin film layer could be formed on the surface of the base material by adsorbing nitrogen as a functional material in a liquid phase and then irradiating the surface with a pulsed laser. [Industrial Applicability]
[0046] According to this embodiment, a functional component (5) is adsorbed onto the surface of a base material (3) and a pulsed laser (23) is irradiated onto the surface of the functional component (5), thereby forming a thin film layer (5) and producing a structural component (1) having the thin film layer (5). Therefore, a structural member (1) having a thin film layer (5) with a complex shape can also be manufactured.
[0047] The thin film layer (5) of the present embodiment can be applied to cutting tools with complicated shapes such as end mills. Since the thin film layer (5) of the present embodiment can improve the hardness and wear resistance and does not peel off, it is possible to improve the cutting performance of the cutting tool and extend its life at the same time.
[0048] The present invention can also be applied to turbine blades for aircraft engines. If the turbine blade is distorted, hydrogen may enter the blade and cause hydrogen embrittlement fracture, but the thin film layer (5) of the present embodiment improves corrosion resistance and does not peel off, making it possible to prevent hydrogen embrittlement fracture. [Explanation of symbols]
[0049] 1 Structural members 3 Basic parts 5 Thin-film layer 21 Lens 23 Pulsed Laser 30 Carbide cutting tip 31 Thin-filmed carbide cutting tip
Claims
1. A base portion of an element member made of a metal material or a ceramic material and configured with a base portion and a surface layer portion located on a surface of the base portion; a thin film layer which is a modified layer of the surface layer portion constituting the base member; It is composed of The base material is a cemented carbide or silicon carbide (SiC), The thin film layer is A surface layer portion of the base member; one or more types of functional components composed of atoms different from the atoms constituting the basic components; and A structural member characterized in that the ratio of atoms constituting the functional member is a gradient structure layer in which the ratio is higher on the surface side of the thin film layer and lower on the interface side with the base portion.
2. 2. The structural member according to claim 1, wherein the thin film layer is formed by doping a surface layer portion of the base member with atoms constituting the functional member by diffusing at an atomic level.
3. 3. The structural member according to claim 1, wherein the atoms constituting the functional member are selected from the group consisting of boron (B), nitrogen (N), carbon (C), oxygen (O), silicon (Si) and titanium (Ti).
4. an adsorption step of adsorbing atoms or molecules as a supply source of one or more types of functional components composed of atoms different from the atoms constituting the base member, in a solid, liquid or gaseous state, on a surface of the surface layer of the base member, the surface layer being composed of a base member and a surface layer located on the surface of the base member, the atoms or molecules being different from the atoms constituting the base member; a diffusion step of irradiating a surface of the surface layer portion constituting the base material with a pulsed laser, or irradiating the surface of the surface layer portion constituting the base material with a pulsed laser while the atoms or molecules as the functional material source are being adsorbed, so that atoms constituting the functional material are diffused and doped at the atomic level into the surface layer portion constituting the base material, thereby forming a thin film layer which is a modified layer of the surface layer portion; having The thin film layer is A surface layer portion of the base member; one or more types of functional components composed of atoms different from the atoms constituting the basic components; and A method for manufacturing a structural member, characterized in that the proportion of atoms constituting the functional member is a gradient structural layer in which the proportion is higher on the surface side of the thin film layer and lower on the interface side with the base portion of the base member.
5. 5. The method for manufacturing a structural member according to claim 4, wherein the pulse width of the pulse laser is from femtoseconds to nanoseconds, and the wavelength is from 300 to 1200 nm.
6. The atoms or molecules serving as the supply source of the functional member are selected from the group consisting of boron (B), nitrogen (N), carbon (C), oxygen (O), silicon (Si), titanium (Ti), boron nitride (BN), boron silicide (SiB), silicide carbon (SiC) and silicon nitride (Si 3 N 4 6. The method for manufacturing a structural member according to claim 4, wherein the metal is selected from the group consisting of:
Citation Information
Patent Citations
Laser implanting and building-up method
JP1990197573A
Tungusten-base sintered alloy with rigidified surface and its production
JP1994172888A
Tool material of zirconium dioxide having modified nitrided surface, modification of the same and production of mutilayer ceramic capacitor using the same tool material of zirconium dioxide
JP1997208308A
Amorphous alloy excellent in bending strength and impact strength, and its production
JP2000026943A
Method for surface-treating cobalt-containing tungsten carbide by irradiation with laser
JP2005298892A